Parents’ Domineering Leadership in “Nanti Kita Cerita Tentang Hari Ini” Movie - Adilla, Annisa; Sunarto, Sunarto (Universitas Veteran Bangun Nusantara, 2022)
This research was entitled “Parents’ Domineering Leadership in “Nanti Kita Cerita Tentang Hari Ini” Movie”. As is known, family conflict discourse had always been one of the debates within the household. Most of family disputes comes from the absence of open communication. Some efforts can be done to minimize conflicts within family scope. After all, family is one of the very first places where people starts to communicate to. This study aims to describe parent’s domineering leadership (father) towards his daughter epicted in “NKCTHI”. The object of the study is “Nanti Kita Cerita Tentang Hari Ini” movie, produced in 2020 by Angga Dwimas Sasongko. The research method uses Roland Barthes’ semiotic analysis through the meaning of lexia and the five existing reading codes. In providing evidences, this research will focus on dialogues and symbols taken from 6 specific scenes. The results indicate that the meaning of lexia occurs in form of restraint, emphasis, blame, and subordination. The study concludes that what is shown in “NKCTHI